Analisis Pengaruh Social Media Marketing Instagram Terhadap Minat Beli Konsumen Kafe Putti Kedaton, Bandar Lampung - Refilia, Deffa; Fornio Barusman, Andoni (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
This study aims to analyze the influence of social media Instagram on consumer buying interest at Putti Cafe, Kedaton Bandar Lampung. This study uses a sampling technique, namely purposive sampling by determining the number of respondents as many as 50 people, which were distributed to cafe Putri consumers directly, the questionnaires were distributed for 2 days. Based on the research that has been done, the results of hypothesis testing produced at count of 18.301 at a significance of 0.00 <0.05 then Ho is rejected and Ha is accepted, which means that attraction (X1) has a positive and significant effect on consumer buying interest (Y). Furthermore, the coefficient of determination test produces a coefficient of determination R2 of 0.875 %, meaning that 875% of consumer buying interest can be explained by social media variables while 12.5% of consumer buying interest is influenced by other unknown variables in this study.